Aktivitas Humas Pemerintah Kota Tangerang Selatan Dalam Program Tempat Pembuangan Sampah Reduce, Reuse, Recyle (3R) - Ghaly Rakha Surya; Winda Dwi Astuti Zebua (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
South Tangerang City Government (Tangsel) is one of the regions in Banten Province, Indonesia, which has been experiencing rapid growth in recent decades. High population growth and urbanization have brought various challenges especially in waste management. Tangsel, like many other cities around the world, is faced with serious problems related to increasing waste volumes and the negative environmental impacts caused by irregular waste disposal. Public Relations activities are organizing reciprocal communication (two ways communications) between a company or an institution and the public which aims to create mutual understanding and support for the achievement of certain goals, policies, activities, production of goods or services and so on for the progress of the company or a positive image for the institution concerned, according to The British Institute Of Public Relations quoted by Ruslan (2020: 16) Public Relations activities in this study. Researchers use qualitative methods, qualitative methods are research that utilizes descriptive data in the form of written or spoken words from people and sources that can be observed. descriptive research type is a research method that utilizes qualitative data in the form of oral written words from people and actors that can be observed and described descriptively. This type of descriptive In the form of written or spoken words from people and sources that can be observed. descriptive research is a research method that utilizes qualitative data in the form of oral written words from people and actors that can be observed and described descriptively. This type of descriptive research is often used to analyze social phenomena or conditions.1. Public Relations Activities of the South Tangerang City Government in Efforts to Instill Awareness and Confidence in the Community stage in the waste management campaign program. Government Public Relations formed a team and assigned it to conduct periodic direct observations throughout the South Tangerang area besides coordinating with all stakeholders such as community leaders, academics, environmental experts, non-governmental organizations and the general public